Potential repellent activity of different herbs powders on periplaneta americana / Masnita Fatihah Md Zahir - Md Zahir, Masnita Fatihah (2017)
This present study was done to assess the effect of herbs for their repellent activity against cockroach, Periplaneta americana. Three different herbs used in this study are Citrus hystrix, Lawsonia inermis and Murraya koenigii. The herbs were prepared in powder form by pulverization method and were applied on the test insects for single and poly herbs plant leaves materials. Single herbs are the single form of the herbs, while poly herbs include 1:1 ratio of mixed concentration of (C.hystrix + L. inermis), (C. hystrix + M. koenigii) and (L. inermis + M. koenigii). The repellency of insects was monitored and recorded at 2, 4, 6 and 24 hour and were statistically analysed for their mean and percentage of repellency. C. hystrix showed the highest repellency in single and poly form while L. inermis and M.koenigii showed low repellency against P. americana in both treatments.